After Copyright: Pwning NFTs in a Clout Economy - Frye, Brian L. (The Columbia Journal of Law & the Arts, 2022)
Copyright is a means to an end, not an end in itself. We created copyright because we wanted to encourage the creation and distribution of works of authorship, not because we wanted to enable copyright owners to control the use of the works they own. We stuck with copyright because it was the best tool we had, despite its flaws. Was copyright ever efficient? No. But marginal improvements matter. Technology has changed the copyright calculus. Distribution of works of authorship gradually got cheaper and cheaper. And then the Internet made it free. But creation remained costly, even though technology helped make it easier. For better or worse, copyright was still our best way of encouraging authors to create new works, by enabling them to claim some of the economic value of those works. Of course, copyright was always a compromise, with many flaws. First, it’s overbroad. While many authors rely on copyright, many others don’t—but copyright protects their works anyway, even if they don’t want it. Second, it’s overlong. Copyright protects works far longer than necessary to encourage their production, and keeps forgotten works out of print. Third, it’s inequitable. By design, copyright only benefits commercially successful authors. And finally, it’s inefficient. Most of the benefits of copyright go to publishers rather than to authors. There’s gotta be a better way. And maybe there is. The market for non-fungible tokens, or “NFTs,” enables authors to sell their works without relying on copyright at all. An NFT is a transferable cryptographic token. Authors can create NFTs that represent “ownership” of their works and sell those NFTs to collectors. The NFT market recognizes the owner of a “legitimate” NFT of a work as the “owner” of the work, even though NFTs typically don’t convey copyright ownership of the work. I call this “pwnership,” because it consists of “clout,” rather than control. NFT owners don’t need copyright, because pwnership depends on the endorsement of the author, rather than control of the use of the work. In fact, NFT owners encourage others to use the work, because popularity increases the value of pwnership. Essentially, NFTs allow authors to profit from creating works of authorship without having to control their use. If the potential profit from selling NFTs alone is large enough to encourage authors to create works, then authors don’t need copyright anymore. And if authors don’t need copyright, no one does. In theory, NFTs could finally make copyright obsolete. Works of authorship are inherently public goods. As Stewart Brand famously observed, “Information wants to be free.” And for most of human history, information was at least nominally free, albeit profoundly costly to obtain. While mechanical reproduction made information far less expensive, it also made the cost of creating and distributing information far more salient. Copyright was the kludge we invented to solve that welcome new problem. We had to destroy free culture in order to save it. Maybe NFTs will enable us to finally dispense with copyright and make information free again.